Moderating effect of education, income and religion on the relationship between information seeking and vaccine-hesitant behaviour among Malaysian parents - Opeyemi, Olowo Emmanuel (2020)
The study was conducted to examine the relationship between demographic factors namely; education, income and religion on vaccine-hesitant behavior. Specifically, this study was conducted to examine the following objectives; i) To identify the type of content of information parents seek when in need of vaccine information, ii) To identify the type of source of information parents use to seek vaccine information, iii) To identify the level of vaccine hesitancy among parents, iv) To examine the relationship between vaccine information seeking (the content of information) and vaccine hesitancy, v) To examine the relationship between vaccine information seeking (source of information) and vaccine hesitancy, vi) To determine how Education moderates the relationship between the content of information and vaccine hesitancy, vii) To determine how Education moderates the relationship between the source of information and vaccine hesitancy, viii) To determine how Income moderates the relationship between the content of information and vaccine hesitancy, x) To determine how Income moderates the relationship between the source of information and vaccine hesitancy, xi) To determine how Religion moderate the relationship between the content of information and vaccine hesitancy and xii) To determine how Religion moderate the relationship between the source of information and vaccine hesitancy. The study has adopted the model introduced by Wilson in 1981. The model explained the information behavior as the activities an individual, person, or group of persons might or may engage in when identifying his/her own need or quest for information, using or transferring that information. The data collection was conducted on 890 respondents from Kedah and Melaka via a set of questionnaires. The questionnaires were distributed to the respondents using the purposive sampling technique. A pilot study was conducted on 100 respondents to check on the validity and reliability of the questionnaire. The data was then analyze using the statistical packages namely AMOS, and SPSS. The findings of the study showed that the content of vaccine information a parent seeks would affect the vaccine behaviour of the parent. The mode of administration of the vaccine either oral or injection had drawn the attention of parents. Vaccine injections were known to cause a little discomfort and side effects and some parents tend to be hesitant towards such a vaccine. The study also showed that the source of vaccine information that had influenced the vaccine behavior among the parents were the internet. Vaccine information was actively retrieved from the internet and social media. Their search for the information was to verify or clarify information about vaccinations. The level of confidence in these information sources will affect the vaccine decision. However, from the study, it was also found that other sources such as radio and television served as passive vaccine information sources. The findings showed that the demographic factors namely the education, income and religion were the moderating factors that affect the vaccine hesitancy among the parents. It was found that the higher the levels of education, income, and religious belief of these parents, the stronger the relationship between the content of information needs, source of information, and vaccine hesitancy. Thus showing that parents who were more educated might seek for more vaccine information from various sources and the more information that they had gathered might also increase their vaccine hesitancy. Similarly, parents from the higher income bracket would also seek more vaccine information and that may also contribute to their vaccine hesitancy. While parents with strong religious belief particularly the Muslim parents may has the vaccine hesitancy when they were unsure of the content of the vaccine. If the content was from the prohibited product, that may have caused for their vaccine hesitancy. However, the study may not be able to be generalized as it only fits the profiles as the respondents used in the study. Therefore, future study should be tailored to respondents that would represent the masses.